SIFAT KOROSIF SURFAKTAN MES (METIL ESTER SULFONAT) DARI MINYAK SAWIT DALAM PEMILIHAN BAHAN SURFACE FACILITIES UNTUK APLIKASI EOR (ENHANCED OIL RECOVERY) - Tajuddin Bantacut dan Wahydin Darmanto TIP (Department of Agroindustrial Technology, Bogor Agricultural University, 2014)
ABSTRACT Petroleum production technology development and application of MES (methyl esther sulfonate surfactant) for EOR (enhanced oil recovery) in Indonesia has very good prospects. The rate of corrosion is one of the important considerations in the application of surfactant in EOR. Therefore, it is necessary to test the corrosion rate caused by MES prior to its application to prevent the failure of the production due to the damage of the metal material used. The purpose of this study was to determine the corrosion rate of MES based surfactant solutions from palm oil on metallic materials (stainless steel 201, stainless steel 304, stainless steel 316, carbon steel and metal galvanist) and to select the most economical metal materials for surface facilities application of MES based surfactant injection. The weight loss method was used to measure the corrosion rate of various types of metal in solution formulation of MES. Corrosion rate in the dilution process (material dissolved before being mixed), has a value that was higher than in the solution that was formulated directly in the mixing tank (mixer). The rate of corrosion of various types of metal being tested were still under 0.127 mm/year or meet the standard rate of corrosion for all surface facilities, machinery and equipment used in oil and gas drilling. Keywords: corrosion rate, surfactant, methyl ester sulfonate, palm oil, surface facilities, enhanced oil recovery